Public goods delivery as a contributing factor to the property tax revenue generation in Malaysian local governments - Kasim, Rozilah; Umar, Muhammad Akilu; Martin, David; Yassin, Azlina Md (American Scientific Publishers, 2018)
Provision of facilities and delivery of strategic services to improve the quality of life the people living in the sub-urban communities is an imperative issue to municipal councils. Similarly, Pasir Gudang Municipal Council (PGMC) is a local government in Malaysia. However, the PGMC property tax assessment revenue generation has decline due to inadequate public goods delivery which tend to have an effect on the amount of property tax assessment revenue generated. The aim of this research is to examine how public goods delivery affects property tax assessment revenue generation at PGMC. Quantitative approach was employed in order to determine how public goods delivery affects property tax revenue generation. Questionnaires are administered to about 300 respondents (taxpayers) using random sampling in order to find out the consequences of insufficient provision of facilities and services. The respondent’s responses were ranked showing the highest and lowest rank according to the questions designed to establish how performance of local government affects its capacity to generate revenue through property tax. The findings from the research show that poor delivery of facilities and services affects the revenue generation. The taxpayers are very observant; if there are no commensurate provisions of facilities and services they avoid paying the property tax assessment because they believe that the revenue generated is not effectively utilized. The study is limited to property tax assessment revenue generation at PGMC. In conclusion, it is observed that sufficient provision of public goods will motivate the taxpayers to settle their property tax assessment. This will inevitably increase the property tax assessment revenue generation and encourage regional development. The research also provides opportunity for future research in the area of service delivery.